Benzalkonium chloride exposure in cats: a retrospective analysis of 245 cases reported to the Veterinary Poisons Information Service (VPIS). (28th February 2015) - Bates, N.; Edwards, N.
Abstract : Benzalkonium chloride is commonly found in household products. This retrospective study examined 245 cases of feline exposure to benzalkonium chloride‐containing products reported to the Veterinary Poisons Information Service (VPIS). A single route of exposure was reported in 188 cats (ingestion 126, skin 58, buccal 4); 57 cats had multiple routes. The common products involved were household antibacterial cleaners (43.6 per cent), household disinfectants (22.3 per cent) and patio cleaners (17.5 per cent). The most common signs were hypersalivation/drooling (53.9 per cent), tongue ulceration (40.4 per cent), hyperthermia (40.4 per cent) and oral ulceration (22.9 per cent). The mean time recorded for onset of the first clinical sign was 6.4 hours (range five minutes to 48 hours, median 4.5 hours, n=60), however, the VPIS was not contacted until 14.0±13.2 hours after exposure (n=120). This figure also reflects the time of presentation. The most common treatments given were antibiotics (82.0 per cent), fluids (50.2 per cent), analgesia (45.3 per cent), gastroprotectants (31.0 per cent), dermal decontamination (24.1 per cent) and steroids (22.7 per cent). 13 cats (5.3 per cent) received syringe or nasogastric feeding. Of 245 cats, 12 (4.9 per cent) remained asymptomatic, 230 (93.9 per cent) recovered and three died (1.2 per cent). The time to recovery ranged from 1 to 360 hours (n=67) with a mean of 100.4±82.0 hours (4.2±3.4 days, median 72 hours).